Adenoidectomy: Anatomical variables as predictive factors of intraoperative adenoid residues. (January 2021) - Pagella, Fabio; Lizzio, Roberta; Pusateri, Alessandro; Ugolini, Sara; Maiorano, Eugenia; Mirabella, Rosolino; De Silvestri, Annalisa; Tinelli, Guido; Matti, Elina
Abstract: Objectives: Adenoid hypertrophy is a common cause of upper airway obstruction in children. However, after adenoidectomy, nasal obstructive symptoms may persist or recur, requiring surgical revision. The aim of this study is to evaluate if individual patient features can influence the efficacy of the traditional technique. Methods: A retrospective observational study was conducted by recruiting patients from candidates for adenoidectomy. All children underwent conventional transoral curettage adenoidectomy with endoscopic control at the end of procedure, and in presence of adenoid residues, a concomitant revision adenoidectomy was performed. For each patient, the following data were collected: age, sex, weight, height, length of the soft palate and surgical technique used. Results: In 18% of patients (113/612), the most critical areas of the nasopharynx were not reached by standard surgery, making a complete adenoidectomy difficult. In this group, the average length of the soft palate was 3.1 cm, 5 mm more than the average of the sample, and 6 mm more than the average length of patients undergoing standard surgery alone ( p  < 0.001). Conclusion: Our study confirms the hypothesis that a greater length of the soft palate conditions the results of the intervention. The length of the soft palate can be considered an intraoperative criterion to select the cases in which perform endoscopic control after the standard procedure.